Homeostasis of Extracellular ATP in Human Erythrocytes - Montalbetti, Nicolas (American Society for Biochemistry and Molecular Biology, 2011)
We explored the intra- and extracellular processes governing the kinetics of extracellular ATP (ATPe) in human erythrocytes stimulated with agents that increase cAMP. Using the luciferin-luciferase reaction in off-line luminometry we found both direct adenylyl cyclase activation by forskolin and indirect activation through β-adrenergic stimulation with isoproterenol-enhanced [ATP]e in a concentration-dependent manner. A mixture (3V) containing a combination of these agents and the phosphodiesterase inhibitor papaverine activated ATP release, leading to a 3-fold increase in [ATP]e, and caused increases in cAMP concentration (3-fold for forskolin + papaverine, and 10-fold for 3V). The pannexin 1 inhibitor carbenoxolone and a pannexin 1 blocking peptide ((10)Panx1) decreased [ATP]e by 75–84%. The residual efflux of ATP resulted from unavoidable mechanical perturbations stimulating a novel, carbenoxolone-insensitive pathway. In real-time luminometry experiments using soluble luciferase, addition of 3V led to an acute increase in [ATP]e to a constant value of ∼1 pmol × (10(6) cells)(−1). A similar treatment using a surface attached luciferase (proA-luc) triggered a rapid accumulation of surface ATP levels to a peak concentration of 2.4 pmol × (10(6) cells)(−1), followed by a slower exponential decay (t(½) = 3.7 min) to a constant value of 1.3 pmol × (10(6) cells)(−1). Both for soluble luciferase and proA-luc, ATP efflux was fully blocked by carbenoxolone, pointing to a 3V-induced mechanism of ATP release mediated by pannexin 1. Ecto-ATPase activity was extremely low (∼28 fmol × (10(6) cells min)(−1)), but nevertheless physiologically relevant considering the high density of erythrocytes in human blood.